Shelf-life Estimation of Instant Pempek Rajungan (Portunus pelagicus) Rancidity with the Arrhenius Acceleration Method - Hanidah, In-In; Sumanti, Debby Moody; Mulyono, Agung Tri; Yusuf, Novy Prakusya (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractRancidity is one of the potential damages to the instant pempek rajungan (Portunus pelagicus) during storage. The purpose of this study was to estimate the shelf life of instant pempek rajungan packed with polypropylene plastic (PP) based on the relationship between storage temperatures and free fatty acids produced. Estimation of shelf life using the acceleration method based on the Arrhenius model. Samples were stored for 30 days at three different temperatures, 25 ± 2 °C, 35 ± 2 °C, and 45 ± 2 °C. The parameter observed during the storage process was an assessment of the rancidity level based on the free fatty acids formed in the sample. Data were analyzed using linear regression and the equation obtained was used to calculate the shelf life of pempek rajungan at room temperature (27 °C). The results showed that the storage time for instant pempek rajungan products at temperatures of 25 ± 2 °C, 35 ± 2 °C, and 45 ± 2 °C could be estimated to be 78, 86, and 70 days respectively with an increase in the number of free fatty acids of 85.2018%, 265.3478%, and 253.1427%.Keywords: Arrhenius, free fatty acid, instant, pempek rajungan, shelf life Abstrak Ketengikan menjadi salah satu potensi kerusakan pempek rajungan instan selama penyimpanan. Tujuan dari penelitian ini untuk menduga umur simpan pempek rajungan instan yang dikemas dengan plastik polypropylene (PP) berdasarkan hubungan antara suhu penyimpanan terhadap asam lemak bebas yang dihasilkan. Pendugaan umur simpan menggunakan metode akselerasi berdasarkan model Arrhenius. Sampel disimpan selama 30 hari pada tiga suhu yang berbeda, yaitu 25 ± 2 °C, 35 ± 2 °C, dan 45 ± 2 °C. Parameter yang diamati selama proses penyimpanan adalah penilaian tingkat ketengikan berdasarkan asam lemak bebas yang terbentuk pada sampel. Data dianalisis menggunakan regresi linier dan persamaan yang diperoleh digunakan untuk menghitung umur simpan pempek pada suhu ruang (27 °C). Hasil penelitian menunjukkan bahwa, waktu penyimpanan produk pempek instan pada suhu 25 ± 2 °C, 35 ± 2 °C, dan 45 ± 2 °C dapat diduga berturut-turut sampai 78, 86, dan 70 hari dengan peningkatan jumlah asam lemak bebas berturut-turut sebesar 85,2018%, 265,3478%, dan 253,1427%.Kata kunci: Arrhenius, asam lemak bebas, instan, pempek rajungan, umur simpan